Two new species of eelpouts (Teleostei, Zoarcidae) of the genus Seleniolycus from the Ross Dependency, Antarctica - Møller, Peter R.; Stewart, Andrew L. (Zootaxa, 2006)
Detailed examination of eelpouts (Zoarcidae) in recently collected material from the Ross Dependency, Antarctica, and held by the Museum of New Zealand Te Papa Tongarewa, revealed two undescribed species of Seleniolycus Anderson, 1988. They both differ from the type species Seleniolycus laevifasciatus (Torno, Tomo & Marschoff, 1977) from the Scotia Sea, Banzarre Bank and Falkland Rise, by having scales on the posterior part of the body (vs. naked), more numerous anal fin rays (69–73 and 64–66 vs. 53–58), total vertebrae (88–97 and 86–89 vs. 74–80), and suborbital head pores (6 and 6–7 vs. 5). Seleniolycus robertsi sp. nov. and S. pectoralis sp. nov. can readily be separated from each other by pectoral fin length (7.9–9.4 vs. 11.1–11.5% SL) and shape (fin entire vs. lower rays exserted), as well as several meristic and morphometric characters. Seleniolycus robertsi inhabits slightly shallower depths than S. pectoralis (1455–2290 vs. 1948–2594 m). The new species have several more generalised character states than Seleniolycus laevifasciatus, and seem to represent the basal-most branch in the Seleniolycus-Melanostigma lineage. A key to the known species of Seleniolycus is provided.